Measuring the Effects through Time of the Influence of Visuomotor and Visuotactile Synchronous Stimulation on a Virtual Body Ownership Illusion. (January 2014) - Kokkinara, Elena; Slater, Mel
Previous studies have examined the experience of owning a virtual surrogate body or body part through specific combinations of cross-modal multisensory stimulation. Both visuomotor (VM) and visuotactile (VT) synchronous stimulation have been shown to be important for inducing a body ownership illusion, each tested separately or both in combination. In this study we compared the relative importance of these two cross-modal correlations, when both are provided in the same immersive virtual reality setup and the same experiment. We systematically manipulated VT and VM contingencies in order to assess their relative role and mutual interaction. Moreover, we present a new method for measuring the induced body ownership illusion through time, by recording reports of breaks in the illusion of ownership ('breaks') throughout the experimental phase. The balance of the evidence, from both questionnaires and analysis of the breaks, suggests that while VM synchronous stimulation contributes the greatest to the attainment of the illusion, a disruption of either (through asynchronous stimulation) contributes equally to the probability of a break in the illusion.